Pendidikan Ruhani Berbasis Kecerdasan Ruhiologi - Iskandar, Iskandar (El-Ghiroh : Jurnal Studi Keislaman, 2022)
National education aims to increase faith, piety, and noble character, which is an aspect of the basic needs of all citizens, in the education process students should receive a strong educational formulation of religious values. This study aims to explore the formulation of national education attainment comprehensively and find new models, or postulates about the formulation of spiritual education based on spiritual intelligence in achieving the main educational goals, namely the achievement of the level of faith, piety and noble character of students. The research method uses descriptive qualitative research. Sources of data sourced from secondary data, namely library data, interview data and field data related to the topics we discussed. While the secondary data aims to support the main data. Data collection techniques collect relevant documents and conduct interviews with related subjects, while data analysis is through data collection, data reduction, data display, verification and data presentation. The results show that the achievement of national education goals in practice has not holistically developed the potential of students, but is more dominant in developing the nature of the mind including cognitive, affective, psychomotor with the Intellectual Quotient (IQ) paradigm approach, Emotional Quotient (EQ), Spiritual Quotient (SQ) so that the educational outcomes meet the legal formalities, while the behavior deviates from the educational outcomes that are not in line with the main national education goals, namely increasing faith, piety and noble character. This illustrates that the attention to the application of the spiritual education dimension of students based on transcendental philosophy is still not focused. Therefore, it is necessary to formulate transcendental-based spiritual education, namely Ruhiologi Quotient (RQ) to be understood by educators and students holistically to guide the IQ, EQ, SQ intelligence paradigm for the achievement of holistic educational goals.